Medos Corriqueiros e Vergonha Cotidiana: Uma análise compreensiva do Bairro do Varjão/Rangel, João Pessoa, PB - Barbosa, Raoni Borges (2015)
This research, from the perspective of anthropology of emotions, aims a comprehensive analysis of the neighborhood of Varjão/Rangel of the city of João Pessoa, Paraíba, as a space of urban sociability of intense personality. The neighborhood is considered one of the most violent and problematic urban quarter of the city. The main hypothesis considered everyday fears and shame as central emotions and as the direct forces of the emotional culture of the neighborhood, as well as of the actions of the residents in the role of interactional units in relation to itself, to another resident, to the neighborhood and to the city. The symbolic-interactionist perspective guided an ethnographic methodology that was held from fieldwork that combined strategies of participant observation and direct interviews. The research results revealed a hierarchical and exclusionary social logic as a central element in the emotional culture of the city of João Pessoa over the peripheral areas of the city, of which the Varjão/Rangel is one of its parts. In this sense, the double neighborhood’s nomination examined here, the official Varjão and the unofficial Rangel as well, demonstrates the impact of moral disputes about the moralizing and modernization process in the city and reflects the everyday stigma, shame and fears as commonplace of an ambiguous and ambivalent identity, the one of the Varjão/Rangel neighborhood. A common resident of the neighborhood, socialized in a tense communicative environment characterized by a deteriorated identity, internalizes the perspective of a "generalized other" that perceives himself as a potentially dangerous character who contaminates the city as a whole. This classificatory logic and argumentation about the neighborhood of the city is taken over by the resident of Varjão/Rangel, who, in turn, hoping to safeguard his face, ends up falling in a play of moral disputes whose logic of excuses and accusations transforms every resident of the neighborhood, including himself, in a branded character.